HOSPITAL LAW: A COMPREHENSIVE REVIEW OF OPERATIONAL ASPECTS, MANAGEMENT, AND LEGAL RESPONSIBILITIES OF HOSPITALS IN THE CONTEXT OF HEALTH SERVICES AND LEGAL PROTECTION FOR MEDICAL PERSONNEL - Hotmaria Hertawaty Sijabat; Gunawan Widjaja (INJOSEDU: International Journal of Social and Education, 2025)
Hospital law in Indonesia comprehensively regulates the operational, managerial, and legal responsibilities of institutions in healthcare services, as stipulated in Law-Law Number 44 of 2009 concerning Hospitals, which emphasises the obligations of good hospital governance, quality control, risk management, and joint liability for systemic negligence such as medical record failures, emergency response, and nosocomial infection control. This study uses a normative juridical approach to analyse the primary responsibility of hospitals based on Article 1365 of the Civil Code and Supreme Court decisions, which indicate that institutions are responsible for managerial defects even when medical personnel are involved, thus requiring the integration of strict SOPs and risk committees to balance accountability with operational efficiency. In parallel, the legal protection of medical personnel is guaranteed through Law-Law Number 29 of 2004 concerning Medical Practice and the principle of error in judicio, with the role of hospitals in supporting vicarious liability, informed consent, and Good Samaritan immunity, despite challenges such as criminal litigation based on Article 351 of the Criminal Code and SLAPP suits demanding reforms such as a national risk guarantee fund to maintain professionalism without sacrificing patient rights. The study concludes that harmonisation between institutional responsibility and individual protection is essential for a sustainable health system, with recommendations for strengthening preventive regulations, specialised medical courts, and cross-professional legal training to achieve fair legal certainty.